PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) BERBANTUAN MEDIA YOUTUBE DALAM PEMBELAJARAN MENULIS TEKS EKSPLANASI PADA SISWA SMA KELAS XI - Kiswari Permatasari; Wikanengsih; Diena San Fauziya (IKIP Siliwangi, 2026)
This research is motivated by the low interest in writing students in learning explanatory texts in grade XI high school students. The purpose of this study was to determine the application of the Problem Based Learning model assisted by YouTube media in learning explanatory texts for grade XI high school students. The subjects of the study involved 33 students of grade XI MIPA 8 SMAN 1 Tempuran. The research method used was a mix method with an exploratory sequential design that combines two research methods, namely qualitative and quantitative methods. Qualitative data were obtained through observation sheets and questionnaires, quantitative data were obtained through tests in the form of pretests and posttests. Based on the results of observations and questionnaires carried out in the learning process using the Problem Based Learning model assisted by YouTube media, it was categorized as very good. The results of the pretest and posttest on the N-gain test obtained an average value of 0.6116. The average value is 30 ≤ N Gain ≤ 70. The average significance level is stated in the